x(3x+7)=0

Simple and best practice solution for x(3x+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(3x+7)=0 equation:


Simplifying
x(3x + 7) = 0

Reorder the terms:
x(7 + 3x) = 0
(7 * x + 3x * x) = 0
(7x + 3x2) = 0

Solving
7x + 3x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(7 + 3x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(7 + 3x)' equal to zero and attempt to solve: Simplifying 7 + 3x = 0 Solving 7 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = 0 + -7 3x = 0 + -7 Combine like terms: 0 + -7 = -7 3x = -7 Divide each side by '3'. x = -2.333333333 Simplifying x = -2.333333333

Solution

x = {0, -2.333333333}

See similar equations:

| -6t+2=-6+2t | | -8-2w=-4w+14 | | -2n+4=7n-77 | | -3d-5=-37-7d | | 5t+4=-116-7t | | -5d-1=-4d-7 | | 2b+7=4b+21 | | 7k-4=17+4k | | x-4=6x-34 | | -t+3=t+7 | | 2n+4=44+7n | | -5a+6=4a-102 | | 6a+4=29+a | | 3a+4=-2+5a | | 6b+8=3b+11 | | 4k-10=-3k+11 | | -8-m=7m-56 | | 10+6m=-2m+90 | | -3+5b=3b+19 | | 2+7n=-3n+112 | | 4(6x+9)=60 | | (2x+4)=(3x+3) | | -2+2b=6b-6 | | -2k+5=-5k+17 | | -9-4n=3n-65 | | 8+3b=-6b-100 | | 4+7d=-5d-8 | | 5w+1=-8-4w | | 3d+6=15+2d | | 9+6a=5a+6 | | 4d+8=80-5d | | 2n^3-n^2-5n=0 |

Equations solver categories